2020
DOI: 10.1111/ijcp.13606
|View full text |Cite
|
Sign up to set email alerts
|

Instruments to assess self‐efficacy among people with cardiovascular disease: A COSMIN systematic review

Abstract: Background: Self-efficacy plays an important role in recovery. There is a need for valid tools that can assess self-efficacy in cardiovascular diseases to provide evidence-based practices. Objective: To perform a psychometric review of self-efficacy instruments in cardiovascular disease according to the COSMIN checklist in order to facilitate the selection of the most suitable measuring instruments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 55 publications
5
5
0
Order By: Relevance
“…The BEES, CSES, SEAMS, and CMSES were categorized as level B, suggesting they may be recommended for use when assessing the target population. A systematic review performed by Kavradim et al (2020) [ 50 ] focusing solely on self-efficacy instruments for cardiac purposes in general population with cardiovascular diseases found similar results which corroborates with our findings to the CSES and CMSES. Another review performed by Lamarche, Tejpal, and Mangin (2018) [ 51 ] assessing self-efficacy instruments in medication management found that SEAMS instrument [ 33 ] is the most appropriate self-efficacy scale.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The BEES, CSES, SEAMS, and CMSES were categorized as level B, suggesting they may be recommended for use when assessing the target population. A systematic review performed by Kavradim et al (2020) [ 50 ] focusing solely on self-efficacy instruments for cardiac purposes in general population with cardiovascular diseases found similar results which corroborates with our findings to the CSES and CMSES. Another review performed by Lamarche, Tejpal, and Mangin (2018) [ 51 ] assessing self-efficacy instruments in medication management found that SEAMS instrument [ 33 ] is the most appropriate self-efficacy scale.…”
Section: Discussionsupporting
confidence: 92%
“…It was observed that the majority of studies presented inconsistent data on the assessed items [ 8 , 31 , 33 , 34 , 36 , 38 – 44 , 46 48 ]. These results are similar with the review by Kavradim et al (2020), which classified CSES with high quality and CMSES with low quality for validity content [ 50 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The mean (standard deviation) for the DSE subscale was 18.41 (4.94), for ESE 20.09 (5.27), and for MSE 19.85 (3.49). The median (lower quartile, upper quartile) for the DSE subscale was 18 (15,21), ESE 20 (16,24), and MSE 20 (18,22). In general, MSE scores were relatively high with the greatest consistency, while DSE and ESE scores were lower with greater variability relative to MSE.…”
Section: Resultsmentioning
confidence: 97%
“…Two widely used validated instruments, the MASES (Medication Adherence Self-Efficacy Scale) and the HBP SCP (High Blood Pressure Self-Care Profile), do measure self-efficacy in hypertension; however, these instruments are limited to medication self-efficacy and were validated in primarily African-American participants [10,12]. A recent meta-analysis describes nine independently validated hypertension self-efficacy instruments [21]. Unfortunately, none encompass the modifiable behaviors of diet, exercise, and medication adherence that are crucial to managing hypertension.…”
Section: Introductionmentioning
confidence: 99%